G474 Variation in patient experience across paediatric diabetes units (pdus) in england and wales and association with glycaemic outcomes. (27th April 2015) - Charalampopoulos, D; Amin, R; Viner, R; Warner, J; Edge, J; Campbell, F; Stephenson, T
Abstract : Background/Aims: Patient: Reported Experience Measures (PREMs) are increasingly recognised as an important indicator of healthcare quality. We investigated variation in patient experience across Paediatric Diabetes Units (PDUs) in England and Wales and explored links between PREMs and glycaemic outcomes. Methods: An aggregate analysis of linked PREM and glycaemic data for each PDU collected as part of the 2012–2013 National Paediatric Diabetes Audit (NPDA) was conducted. The percentage of patients/carers who reported a high level of satisfaction (scores 9 or 10/10) in the friends and family recommendation test was used as a quality indicator of diabetes care. A funnel plot of the above indicator was constructed and the 95% and 99.8% control limits around the mean were used to distinguish between common–cause (units lying within the control limits) and special-cause variation (units lying outside the control limits). A linear regression model was also fitted for the relationship between mean satisfaction score and mean HbA1c at PDU level. Results: Percentage of patients who reported high satisfaction showed a 2.9-fold variation (range 35% to 100%) across PDUs with 60/170 (35.3%) and 33/170 (19.4%) units falling outside the 95% and the 99.8% control limits respectively. Of the 170 PDUs, 21 (12.4%) lay below the lower 99.8% control limit (Figure 1 ). Linear regression showed a significant negative association between mean HbA1c (mmol/mol) and average satisfaction score for each PDU (regression coefficient= –2.9, 95% CI: –4.7 to –1.1, p = 0.002) (Figure 2 ). Conclusion: Patient satisfaction varied considerably across PDUs with one in three units exhibiting more variation than expected by chance. At aggregate level, clinics with higher mean satisfaction had better average glycaemic control. Individual-level analyses allowing for nested sources of variation (patients within clinics) are needed to confirm these clinic-level analyses. Further work should also adjust for "case-mix variation" i.e. correct for differences in the sociodemographic and disease profile of children served by different clinics.